2018
DOI: 10.1111/jcmm.13827
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a GNE homozygous mutation in a Han‐Chinese family with GNE myopathy

Abstract: GNE myopathy is a rare, recessively inherited, early adult‐onset myopathy, characterized by distal and proximal muscle degeneration which often spares the quadriceps. It is caused by mutations in the UDP‐N‐acetylglucosamine 2‐epimerase/N‐acetylmannosamine kinase gene (GNE). This study aimed to identify the disease‐causing mutation in a three‐generation Han‐Chinese family with members who have been diagnosed with myopathy. A homozygous missense mutation, c.1627G>A (p.V543M) in the GNE gene co‐segregates with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Compared with other reports, these twins are some of the youngest reported and their baseline platelet counts were of the lowest values when they were diagnosed. Consistent with other reports [ 17 , 19 , 20 ], mutations in GNE associated with thrombocytopenia were within the N-acetylmannosamine (ManNAc) kinase domains of the GNE protein. Thus, this domain may be an interesting site for further investigation related to congenital thrombocytopenia associated with GNE mutations.…”
Section: Discussionsupporting
confidence: 90%
“…Compared with other reports, these twins are some of the youngest reported and their baseline platelet counts were of the lowest values when they were diagnosed. Consistent with other reports [ 17 , 19 , 20 ], mutations in GNE associated with thrombocytopenia were within the N-acetylmannosamine (ManNAc) kinase domains of the GNE protein. Thus, this domain may be an interesting site for further investigation related to congenital thrombocytopenia associated with GNE mutations.…”
Section: Discussionsupporting
confidence: 90%
“… 1 The incidence rate of GNE myopathy ranged from 1 to 21 per million. 2 , 3 The clinical manifestations include distal extremity weakness with early adult‐onset, especially foot drop due to the slowly progressive weakness of the anterior tibialis muscle, with quadriceps femoris relatively unaffected. Pathological manifestations of muscle biopsy are prominent rimmed vacuoles without inflammatory response, which can especially be found in atrophied muscle fiber.…”
Section: Introductionmentioning
confidence: 99%
“…This disease is also known as distal myopathy with rimmed vacuoles (DMRV) disease or Nonaka myopathy 1 . The incidence rate of GNE myopathy ranged from 1 to 21 per million 2,3 . The clinical manifestations include distal extremity weakness with early adult‐onset, especially foot drop due to the slowly progressive weakness of the anterior tibialis muscle, with quadriceps femoris relatively unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with kinase domain mutations progress faster than those with heterozygous mutations in terms of joint function [ 6 ]. It is suggested that different variants have different effects on function [ 7 ]. The spectrum of diseases caused by GNE mutations has continued to increase in recent years.…”
Section: Introductionmentioning
confidence: 99%